Integration of healthcare programs: A long-term policy perspective for a sustainable HIV program for India - Sukarma S.S. Tanwar; Bharat B Rewari (Wolters Kluwer Medknow Publications, 2013)
With the Government of India's initiative to ensure Universal Access to health through its flagship program of National Rural Health Mission, the debate on the economic efficiency and sustainability of a 'stand-alone' over 'integrated' programs has become extremely relevant. This study was conducted with the aim to establish opinion on the issue of sustainability of 'stand-alone' HIV program in India. Experts working on health policy development and implementation at various were interviewed on this issue and majority of experts interviewed were of the opinion that a 'stand-alone' HIV program is not sustainable in the long run because of inefficient use of resources. Integration of HIV program with the general health system is essential but it needs extensive planning. Areas like HIV testing centers, prevention of parent to child transmission and sexually transmitted infection diagnosis and treatment can be integrated with the general health system immediately.